The Effect Of Glass-Ceramic (GC) Filled Poly(Methyl Methacrylate) Bone Cement Composites - Samad, Hamizah Abdul (2011)
In this study, a composition of glass-ceramic was fabricated based on the Na2O-CaO-SiO2 glass system and was used as filler in commercial PMMA bone cement (PALACOS LV®). In producing the glass-ceramic powder, firstly the glass powders were analyzed using DSC/TGA and XRF, then it was compacted and heat treated at temperatures between 850 to 1000oC. XRD result of glass-ceramic heat treated at 950oC shows high crystallization of wollastonite (CaSiO3) and sodium calcium silicate, (Na2Ca3Si6O16) in the glass composition.